2013
DOI: 10.1590/s0004-27302013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Efeito in vitro da triiodotironina sob o potencial osteogênico reduzido de células-tronco mesenquimais do tecido adiposo de ratas ovariectomizadas e com osteoporose

Abstract: OBJETIVO: Avaliar se a triiodotironina (T3) aumenta a diferenciação osteogênica das células-tronco mesenquimais do tecido adiposo (CTM-TA) de ratas adultas ovariectomizadas e com osteoporose e compará-lo ao de ratas adultas e jovens sem osteoporose. MATERIAIS E MÉTODOS: CTM-TA foram cultivadas em meio osteogênico e distribuídas em sete grupos: 1) CTM-TA de ratas jovens sem osteoporose; 2) CTM-TA de ratas adultas sem osteoporose; 3) CTM-TA de ratas adultas com osteoporose e 4, 5, 6 e 7) CTM-TA de ratas adultas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Multiple studies have already demonstrated the participation of mesenchymal stem cells in the genesis of osteopenia induced by endocrine diseases such as hypo and hyperthyroidism (Boeloni et al, 2010;Boeloni et al, 2013a;Boeloni et al, 2013b;Boeloni et al, 2013c;Boeloni et al, 2015) and diabetes (Zhao et al, 2013;Ha et al, 2015). Although receptors for prolactin have already been identified in human mesenchymal stem cells, this seems to be the first study that investigated the effects of prolactin in the osteogenic differentiation of adipose tissue-derived mesenchymal stem cells.…”
mentioning
confidence: 99%
“…Multiple studies have already demonstrated the participation of mesenchymal stem cells in the genesis of osteopenia induced by endocrine diseases such as hypo and hyperthyroidism (Boeloni et al, 2010;Boeloni et al, 2013a;Boeloni et al, 2013b;Boeloni et al, 2013c;Boeloni et al, 2015) and diabetes (Zhao et al, 2013;Ha et al, 2015). Although receptors for prolactin have already been identified in human mesenchymal stem cells, this seems to be the first study that investigated the effects of prolactin in the osteogenic differentiation of adipose tissue-derived mesenchymal stem cells.…”
mentioning
confidence: 99%